Differential induction of interleukin-1beta and tumour necrosis factor-alpha may account for specific patterns of leukocyte recruitment in the brain. - Blond, D; Campbell, S; Butchart, A; Perry, V; Anthony, D (2002)
In peripheral tissue, IL-1beta has been shown to induce TNFalpha expression and vice versa, resulting in mixed neutrophil and mononuclear cell recruitment to the site of injury. This has led to the concept of crosstalk in peripheral cytokine signalling pathways. In the brain parenchyma, however, restricted patterns of leukocyte recruitment following the focal injection of pro-inflammatory agents into the brain are observed. This study investigates the expression of the principal pro-inflammatory cytokines--IL-1beta and TNFalpha--in the brain after IL-1beta, TNFalpha, NMDA or endotoxin injection into the brain parenchyma of rats. Each of these agents gives rise to a distinct pattern of acute leukocyte recruitment at 24 h. We found that IL-1beta induces de novo synthesis of additional IL-1beta but not TNFalpha, as determined by RT-PCR and ELISA, and TNFalpha does not induce either itself or IL-1beta. Injection of NMDA results in IL-1beta, but not TNFalpha up-regulation. Injection of IL-1beta or NMDA is associated with neutrophil recruitment whereas injection of TNFalpha is associated with mononuclear cell recruitment. Following injection of endotoxin, both TNFalpha and IL-1beta levels are elevated and neutrophils and mononuclear cells are recruited to the brain. These data suggest that the signalling pathways that are present in the periphery are modified in the brain and that differential induction of TNFalpha and IL-1beta may have a role in the atypical pattern of leukocyte recruitment observed in the brain.